ANALISIS KEPUASAN KONSUMEN TERHADAP KUALITAS PELAYANAN DAN JASA DENGAN MENGGUNAKAN METODE IMPORTANCE PERFORMANCE ANALYSIS (Studi Kasus di Restoran Warung Subak, Peguyangan Denpasar) - Manik Iswari, I A Istri; Wiranatha, A.A.P. Agung Suryawan; Satriawan, I Ketut (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 3 No 3 (2015): September)
Consumer satisfaction is consumer response to evaluation of incompatibility between previously expectations to the actual performance that is felt after use. The aim of this research is to determine the attributes that are considered important by consumers in order to achieve customer satisfaction. The study was conducted in Restaurant Warung Subak Peguyangan Denpasar. Sampling is with purposive sampling method and data was collected by distributed questionnaires and interview directly some respondents. Analyzed was undertaken by used Importance Performance Analysis technique and Cartesian diagram. The results showed that the highest consumer satisfaction was the attribute no.1 were Warung Subak has meeting room facilities, wifi, parking, toilet with the compatibility level of 98,3%. The lowest level of compatibility is the attribute no. 7 are Warung Subak serves consumers fastly in a short time and soon with the compatibility level of 80,1%. Quadrant A showed the attributes that are considered important and get priority of the company based on the level of importance and performance was the attribute no.2 were Warung Subak had a strategic location, attribute no.7 were Warung Subak serves consumers fastly in a short time and soon and the attributes no.8 were good processing of food and beverages at Warung Subak.
Keywords: 57,